Reassessing L2 sensitivity to island constraints: asymmetries between wh-islands and adjunct-islands - Kim, Boyoung (Frontiers in Language Sciences, 2025)
This study investigates Korean L2 speakers' sensitivity to English island constraints, focusing on the widely reported—but theoretically puzzling—asymmetry between wh/whether-islands and adjunct-islands. Using a factorial definition of island effects, we quantified island penalties while independently estimating the costs of dependency-length and structural-complexity, two factors commonly assumed to interact with the unacceptability of island violations. Acceptability judgment results showed that native speakers displayed robust island effects across all types, whereas L2 speakers displayed significant effects for adjuncts (because- and when-clauses) and whether-islands but no statistically reliable island effect for wh-islands. The overall magnitude of island effects was smaller in L2 speakers and decreased systematically with later Age of Arrival (AoA). Despite these differences, both groups exhibited the same gradient hierarchy of island strength (wh<whether < adjuncts) and comparable structural-complexity costs (wh > whether > adjuncts), indicating fundamentally similar island representations and processing demands across groups. L2 speakers, however, showed greater dependency-length costs—indicating greater difficulty with long-distance dependencies, especially with later AoA—which appear to reduce the contrast between non-island and island configurations, yielding smaller observable island effects. This pattern was most pronounced for wh-islands, which combine high structural complexity with the weakest island effects, creating the appearance of an L2-specific asymmetry despite otherwise native-like sensitivity. Overall, the findings suggest that L2 speakers' island sensitivity is native-like in kind but reduced in degree, reflecting quantitative rather than qualitative differences between groups.